Observations on morphology of immature Lucilia porphyrina (Diptera: Calliphoridae), a fly species of forensic importance - Tunwadee Klong-Klaew (2018)
Lucilia porphyrina (Walker) is a blow fly of forensic importance, and shares its geographical distribution with a related forensically important species, Lucilia cuprina (Wiedemann). The immature stages of both species are similar in general appearance; therefore, correct identification should be given special consideration. This study highlighted the main features of L. porphyrina larvae, as observed under light microscopy and scanning electron microscopy. Particular attention is given to the anterior and posterior spiracles, cephalopharyngeal skeleton, and characteristics of the dorsal spines between the prothorax and mesothorax. In the third instar specifically, morphological information on L. porphyrina showed several features that are shared by L. cuprina, and therefore need certain identification to distinguish between them. Such key features are (1) greater posterior spiracle, (2) apparent inner projection between the middle and lower slits of the posterior spiracle, and (3) strongly sclerotized peritreme. The number of papillae on the anterior spiracle may be a supplement, five to nine and three to six in L. porphyrina and L. cuprina, respectively. The key for identifying third instar of forensically important flies in Thailand has been updated to include L. porphyrina. © 2012 Springer-Verlag.